Paracoccidioidomycosis: Current Perspectives from Brazil - Mendes, Rinaldo Poncio; Cavalcante, Ricardo de Souza; Marques, Sílvio Alencar; Marques, Mariângela Esther Alencar; Venturini, James; Sylvestre, Tatiane Fernanda; Paniago, Anamaria Mello Miranda; Pereira, Ana Carla; da Silva, Julhiany de Fátima; Fabro, Alexandre Todorovic; Bosco, Sandra de Moraes Gimenes; Bagagli, Eduardo; et al. (The open microbiology journal, 2017)
This review article summarizes and updates the knowledge on paracoccidioidomycosis. and the cryptic species of and their geographical distribution in Latin America, explaining the difficulties observed in the serological diagnosis. Emphasis has been placed on some genetic factors as predisposing condition for paracoccidioidomycosis. Veterinary aspects were focused, showing the wide distribution of infection among animals. The cell-mediated immunity was better characterized, incorporating the recent findings. Serological methods for diagnosis were also compared for their parameters of accuracy, including the analysis of relapse. Clinical forms have been better classified in order to include the pictures less frequently observesiod. Itraconazole and the trimethoprim-sulfamethoxazole combination was compared regarding efficacy, effectiveness and safety, demonstrating that azole should be the first choice in the treatment of paracoccidioidomycosis.